Human immune response to SARS-CoV-2 infection - Wina Nurtias, Lia Yosaneri; Rahma Turista, Dora Dayu; Puspitasari, Eka (Jurnal Teknologi Laboratorium, 2020)
COVID-19 is an acute respiratory infection caused by a new type of Coronavirus, SARS-CoV-2, which first appeared in Wuhan, China in December 2019. COVID-19 then became a pandemic in various countries in early 2020. In this article it contains review that discusses the immune response in humans due to SARS-CoV-2 infection, using the narrative literature review method, a total of 36 articles (6 from Elsevier, 24 from PMC, and 6 from Springer). It is known that the pathogenesis of COVID-19 and the manufacture of drugs and vaccines are still under investigation, but in infected patients, innate immune responses in the form of alveolar macrophages, dendritic cells, airway epithelial cells, congenital lymphocytes, and neutrophils work together in the fight against infection. Next comes the adaptive immune response in the form of antibodies (immunoglobulins) which help in fighting infections due to SARS-CoV-2. These immune responses include increasing levels of cytokines, coagulation parameters, C-reactive protein, neutrophils, and decreasing total lymphocytes. It is also known that COVID-19 patients with severe disease often experience higher total antibody, IgM responses, and IgG responses than COVID-19 patients without congenital disease. IgG antibodies are present in the serum, so the serum in COVID-19 patients who have recovered can be used for therapy in COVID-19 patients who have not healed, as long as the drug and vaccine are under investigation.